Peningkatan Kemampuan Mesin Bubut untuk Pemesinan Proses Freis dengan Menambahkan Alat Bantu Cekam - Dimas wicaksono; Muhammad Yanis; M. A. Ade Saputra (Jurnal Rekayasa Mesin, 2023)
Fixtures are made and designed specifically to help the manufacturing process. The function of this fixture is to save costs, ensure thorough product quality, reduce waiting time and increase production results. In this research, efforts were made to increase the productivity capabilities of lathe machines by adding a fixture. This fixture is used to carry out face milling and drilling processes on flat surface workpieces. This additional equipment is installed on the lathe to replace the tool post and its function is to grip the workpiece to be machined. The cutting tool is held on the lathe spindle directly or using a special spindle shaft. With this condition, where the workpiece experiences a feed motion and meanwhile a cutting motion by the cutting tool, the process is the same as on a milling machine. The fixture made is as expected, which based on accuracy testing and running tests shows that machining errors and deviations are within the standardized range of 0.4 to 25 µm.